PENGEMBANGAN MODUL AJAR INOVATIF BERBASIS ETNOBUDAYA BATAK TOBA UNTUK MENINGKATKAN LITERASI BUDAYA - Purba, Nancy Angelia; Eva Pratiwi Pane; Jennifer Demi Arta Simamora (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2025)
This study was motivated by the low level of cultural literacy among PGSD UHKBPNP students concerning Batak Toba culture, due to the lack of teaching materials integrating local values. The objective of this research is to develop an innovative teaching module based on Batak Toba ethnoculture to enhance students’ cultural literacy. The research employed a development method using the Nieveen, McKenney, and Van den Akker model, which consists of three stages: preliminary, development, and evaluation. The research instruments included expert validation sheets and cultural literacy tests (pretest–posttest) administered to 45 PGSD students enrolled in the Advanced Indonesian Language Learning course. Validation results by experts indicated that the module achieved an average score of 88.5%, categorized as very good. Effectiveness testing using n-gain analysis showed a significant improvement in students’ cultural literacy, with average pretest and posttest scores of 56.2 and 82.4, respectively, and an n-gain value of 0.59 (medium–high category). These findings demonstrate that the innovative Batak Toba ethnocultural-based teaching module is valid, practical, and effective in improving students’ cultural literacy. The development of this module contributes to strengthening students’ cultural identity and supports the preservation of local culture in the globalization era. Keywords: Teaching module, Batak Toba ethnoculture, Cultural literacy